A balanced output CMOS OTA with wide linear current tunable range - Kaewdang, Khanittha; Surakampontorn, Wanlop (My University, 2011)
A new CMOS-based balanced output operational transconductance amplifier (BOTA) with very wide linear current tunable range is proposed in this paper. The design technique is achieved by the combination of a fully differential transconductor and an electronically variable current gain stage. The transconductance gain of the proposed BOTA can be linearly tuned by an external bias current for more than 4 decades, with less than 4% nonlinearity for the linear input-voltage range of about 0.2 Vpeak. The OTA is designed in 0.5 μm AMIS technology. The performance of the proposed circuit is discussed and confirmed through application example and PSPICE simulation results. © 2010 Elsevier GmbH. All rights reserved.
Keywords: Balanced output operational transconductance amplifier (BOTA); CMOS transconductor; Electronically tunable OTA; Linearly tuned